PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP ALOKASI BELANJA MODAL DENGAN LUAS WILAYAH SEBAGAI VARIABEL MODERASI (Studi Empiris pada Kabupaten/Kota di Provinsi Sumatera Utara Tahun 2014- 2016) - Lamido, Ivan; Ratnawati, Vince; Susilatri, Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to know the influences of Local Revenue and General Allocation Funds to Capital Expenditure with area as variable moderating. The population of this study is all the city/regency in Province North Sumatera period 2014-2016. All of the population are sample. The Method of analysis uses multiple linear regression. The results of testing that has been done. Partial regression test (t test) showed that the Local Revenue has effect to capital expenditure with P<0,05 (P= 0,000). General Allocation Funds has no effect to capital expenditure with P>0,05 (P=0,448). The result of this study also show that area do not moderate the effect of local revenue and general allocation fund to capital expenditure.Keywords : local revenue, general allocation funds, capital expenditure, area